The Fourth Industrial Revolution as a Catalyst for Banking Performance Improvement -A Reading of the National Bank of Algeria's Experience- - kerdouci, asma; kerdouci, meriem (Journal of Research in Finance and Accounting, 2025)
The study aims to shed light on the radical transformations brought about by the Fourth Industrial Revolution in the banking sector and their impact on bank performance. This study relies on quantitative and qualitative research tools and evaluates the experience of the National Bank of Algeria (BNA), a pioneer in the Algerian banking sector in introducing modern technologies. This study analyzes key indicators that reflect the use of these technologies in digitizing its banking services and measures their impact on banking performance. The study concludes that the National Bank of Algeria has achieved success in utilizing modern technologies, demonstrating the effectiveness of its established digital strategies aimed at improving the customer experience by providing innovative and flexible banking services that meet customers' financial needs and align with their desires. However, the National Bank of Algeria still faces some challenges that pose a real obstacle to ensuring the continuity of its approach to digital progress and modernization.